Joseph Conrad and psychological medicine - Bock, Martin, 1951- (Texas Tech University Press, 2002)
Conrad's life and fiction are often read through the lens of Freudian thought, though Conrad understood his own health from a pre-Freudian perspective. Joseph Conrad and Psychological Medicine recovers that perspective, revises our understanding of Conrad's life, and rethinks the dominant themes of his work in light of pre-Freudian medical psychology. Beginning with a social history of late-nineteenth-century medical psychology and hysteria studies, Bock's study presents a clear and readable synopsis of fin-de-siècle theories of nervous disorder and moral insanity, shows how Conrad's doctors were trained in medical theories that privilege the physiological over the psychological, and describes what Conrad endured during his water cures at Champel-les-Bains and in an English culture that constructed nervous disease-particularly his diagnosed neurasthenia-as a feminine disorder. Joseph Conrad and Psychological Medicine reads Conrad's fiction medically, showing how Conrad's work focuses on such narrative strategies as Conrad's rhetoric of hysteria and enervation and his vivid, nervous descriptions, and it shows how major tropes such as restraint, seclusion, and water- all treatments for insanity-were important issues in the medical discourse of Conrad's day and are themes that run through Conrad's fiction. Bock's study also suggests that Conrad's major breakdown of 1910 was an epiphany, an event Conrad feared for decades but that afterwards allowed him to shift the interests of his fiction. The post-breakdown fiction offers less brooding and more allegorized narrations of Conrad's medical history as he moves towards a greater acceptance, late in his life, of his gender and sexuality.